Proposal for coordinated health research in PFAS-contaminated communities in the United States - Thomas A. Bruton; Arlene Blum (BMC, 2017)
Abstract The drinking water of more than six million Americans in numerous communities has been found to contain highly fluorinated chemicals at concentrations of concern. Certain of these chemicals, including perfluorooctanoic acid and perfluorooctane sulfonic acid, are known to be persistent, bioaccumulative, and associated with adverse health outcomes in humans and animal models. The possible health impacts of exposure to highly fluorinated chemicals are of great concern to communities whose water has been impacted. Community members want information, and are asking for biomonitoring, exposure pathway analysis, and health studies. Governmental agencies are striving to deal with these multiple concerns in the face of information and resource constraints. We propose the development of a high-level research strategy to maximize what can be learned about health effects of highly fluorinated chemicals and methods to reduce or eliminate exposure. We suggest coordinating the research across multiple communities for greater statistical power. If implemented, such a strategy could help to generate information and evidence integration to enable regulatory decision making and contribute to reducing future exposures.